Resposta :
Resposta:
Para a alternativa A, se for [tex]f(x)=x^{2} -4x-4[/tex], teremos:
Para a alternativa B, se for [tex]f(x)=x^{2} +4x-4[/tex], teremos:
Para a alternativa C, se for [tex]f(x)=2x^{2} -5[/tex], teremos:
[IMAGENS EM ANEXO NOMEADAS]
![Ver imagem АНОНИМ](https://pt-static.z-dn.net/files/d13/4be1efad2c581347dd64741592dab6a4.jpeg)
![Ver imagem АНОНИМ](https://pt-static.z-dn.net/files/dd2/92fd4cb09b85228c3d57e68693e1adb7.jpeg)
![Ver imagem АНОНИМ](https://pt-static.z-dn.net/files/d93/38a9fed05a387322aca526d77a1c9643.jpeg)
Resposta:
Para a alternativa A, se for [tex]f(x)=x^{2} -4x-4[/tex], teremos:
Para a alternativa B, se for [tex]f(x)=x^{2} +4x-4[/tex], teremos:
Para a alternativa C, se for [tex]f(x)=2x^{2} -5[/tex], teremos:
[IMAGENS EM ANEXO NOMEADAS]